Visual conversations - Bramston, Dave, ....- (Lausanne : AVA Academia, 2010)
Basics Product Design: Visual Conversations introduces design students to the art of communication in design. Throughout the book, David Bramston explains the process of translation from rough concept to fully realised production, emphasising the importance of simplicity in creating effective sketches. There is also an examination of the many methods you can use to elicit an emotional response and an exploration of the physical realisation of ideas. Basics Product Design: Visual Conversations puts design theory into a real-world context with beautiful examples and case studies from some of the world's leading designers and artists. The title comprises a comprehensive introduction to the language of product design.
Includes bibliographical references.
Keywords: Industrial design -- Methodology; New products; Industrial design -- Case studies; New products -- Case studies